Duševné vlastníctvo ako generátor inovácií - Helena Majdúchová; Denisa Gajdová; Monika Jančovičová (Trendy v podnikání, 2018)
Small and medium enterprises play an important role in economy of Slovak Republic and European Union. Importance of innovation for small and medium enterprises increase with the dynamism of economic environment. Innovation is joined with concepts as improvement, increase of profit, increasing of effectiveness, competiveness growth, technological improvement, artificial intelligence, intellectual property etc. One of determining factor by which creativity and innovation in whole economy could be supported is effective system of Intellectual property rights. The aim of this article is to determine and evaluate situation of intellectual property activities realisation in the area of small and medium enterprises in Slovakia. We consider Intellectual property in conjunction with implementation of outcomes of research and development as the important determinant of SME ́s innovation potential.